HISTORICAL AND CULTURAL ASPECTS OF TRADITIONAL CRAFTS TEACHING IN PRE-IMPERIAL AND IMPERIAL CHINA (based on a pottery industry) - Zhenghui, Wu; Weijie, Chen (Pedagogy and Psychology, 2022)
This Article gives consideration to the development of the ceramic art during the pre-imperial and imperial era in China. It is considered through the lens of the craft teaching methods applied in the art of ceramics. The authors of the Article base on the idea that the traditional system of ceramists teaching, which dates back several millennia, was forming along with the formation of the pottery industry itself and this is well-argued on the basis of historical, art and educational research aspects. The authors of the Article are convinced that a short historical tour performed back to the origins of the pottery industry will make it possible to trace a genesis of formation and features of the ceramic art teaching during the pre-imperial and imperial periods of China. Indeed, these are the periods when the fundamentals of the entire art professional education system of China were established, and then this system was spread out for many centuries ahead. As a result of the given research we have a conclusion that during the above mentioned periods in the traditional Chinese culture there was a cult of a teacher and the entire traditional crafts teaching system, including the pottery teaching, among others, was founded on the apprenticeship principles, i.e. «an apprentice under a master craftsman» principle. Starting from the establishment of the first states in China, there a great importance was given to the development of the handicrafts, the imperial workshops were dynamically organized and they became the first breeding grounds for training the future excellent master craftsmen.